Effectiveness of rehabilitation interventions to improve paretic propulsion in individuals with stroke – A systematic review. (January 2020) - Alingh, J.F.; Groen, B.E.; Van Asseldonk, E.H.F.; Geurts, A.C.H.; Weerdesteyn, V.
Abstract: Background: Stroke survivors often show reduced walking velocity and gait asymmetry. These gait abnormalities are associated with reduced propulsion of the paretic leg. This review aimed to provide an overview of the potential effectiveness of post-stroke rehabilitation interventions to improve paretic propulsion, ankle kinetics and walking velocity. Methods: A systematic search was performed in Pubmed, Web of Science, Embase, and Pedro. Studies were eligible if they reported changes in propulsion measures (impulse, peak value and symmetry ratios) or ankle kinetics (moment and power) following intervention in stroke survivors (group size ≥10). Study selection, data extraction and quality assessment were performed independently by two authors. Findings: A total of 28 studies were included, of which 25 studies applied exercise interventions, two studies focused on surgical interventions, and one on non-invasive brain stimulation. The number of high-quality trials was limited ( N  = 6; score Downs and Black scale ≥19). Propulsion measures were the primary outcome in eight studies. In general, mixed results were reported with 14 interventions yielding improvements in propulsion and ankle kinetics. In contrast, gains in walking velocity were observed in the vast majority of studies ( N  = 20 out of 23). Interpretation: Interventions that yielded gains in propulsion appeared to have in common that they challenged and/or enabled the utilization of latent propulsive capacity of the paretic leg during walking. Walking speed generally increased, regardless of the observed change in propulsion, suggesting the use of compensatory mechanisms. Findings should, however, be interpreted with some caution, as the evidence base for this emerging focus of rehabilitation is limited. Highlights: This paper reviews the effects of interventions on paretic propulsion post stroke. Out of 28 included studies, only 6 studies were of high methodological quality. Interventions concerned exercise therapy (with or without technology) and surgery. Intervention effects on propulsion measures and ankle kinetics were mixed. Interventions that challenge or enable latent propulsive capacity show promise.